2015
DOI: 10.1063/1.4929819
|View full text |Cite
|
Sign up to set email alerts
|

Photo-acoustic spectroscopy and quantum efficiency of Yb3+ doped alumino silicate glasses

Abstract: In this contribution, we analyze the effect of several preparation methods of Yb3+ doped alumino silicate glasses on their quantum efficiency by using photo-acoustic measurements in comparison to standard measurement methods including the determination via the fluorescence lifetime and an integrating sphere setup. The preparation methods focused on decreasing the OH concentration by means of fluorine-substitution and/or applying dry melting atmospheres, which led to an increase in the measured fluorescence lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Recently, several studies on rare earth doped aluminosilicate glasses were published. As dopants, ytterbium, samarium, europium, and other ions were used [ 11 , 12 , 13 , 14 ]. It was shown that the base composition of glass has a strong impact on the luminescence properties of the dopant rare earth ions, e.g., the spectral shape of their absorption and emission spectra as well as their luminescence lifetimes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies on rare earth doped aluminosilicate glasses were published. As dopants, ytterbium, samarium, europium, and other ions were used [ 11 , 12 , 13 , 14 ]. It was shown that the base composition of glass has a strong impact on the luminescence properties of the dopant rare earth ions, e.g., the spectral shape of their absorption and emission spectra as well as their luminescence lifetimes.…”
Section: Introductionmentioning
confidence: 99%
“…Since for lower temperatures the probability of multi-phonon processes is reduced, early samples with higher OH-concentrations showed a significant temperature dependence, while the low OH sample remained nearly unaffected. This suggests that these samples reach a pretty good quantum efficiency, which was also confirmed by photo acoustic measurements [13].…”
Section: Spectroscopic Investigationsmentioning
confidence: 52%
“…Consequently in this special case, the PA-measurements can be used to determine whether the particle concentration has an influence on the thermal diffusivity DS of the samples in comparison to the pristine P(VDF-TrFE) 70/30, for which DS=1.09·103 cm2/normals [39]. The specific PA measurements were carried out using an experimental setup described in [48] (Figure 2a). This setup was supplemented by a polished brass cylinder (4 mm thickness, 8 mm diameter, Figure 2b), placed inside the photoacoustic cell to decrease the volume of the gas tight chamber resulting in an increased SA.…”
Section: Methodsmentioning
confidence: 99%